Conventional protein kinase Cβ‐mediated phosphorylation inhibits collapsin response‐mediated protein 2 proteolysis and alleviates ischemic injury in cultured cortical neurons and ischemic stroke‐induced mice. Issue 3 (11th February 2016) - Yang, Xuan; Zhang, Xinxin; Li, Yun; Han, Song; Howells, David W.; Li, Shujuan; Li, Junfa
Abstract: We previously reported that conventional protein kinase C (cPKC)β participated in hypoxic preconditioning‐induced neuroprotection against cerebral ischemic injury, and collapsin response‐mediated protein 2 (CRMP2) was identified as a cPKCβ interacting protein. In this study, we explored the regulation of CRMP2 phosphorylation and proteolysis by cPKCβ, and their role in ischemic injury of oxygen–glucose deprivation (OGD)‐treated cortical neurons and brains of mice with middle cerebral artery occlusion‐induced ischemic stroke. The results demonstrated that cPKCβ‐mediated CRMP2 phosphorylation via the cPKCβ‐selective activator 12‐deoxyphorbol 13‐phenylacetate 20‐acetate (DOPPA) and inhibition of calpain‐mediated CRMP2 proteolysis by calpeptin and a fusing peptide containing TAT peptide and the calpain cleavage site of CRMP2 (TAT‐CRMP2) protected neurons against OGD‐induced cell death through inhibiting CRMP2 proteolysis in cultured cortical neurons. The OGD‐induced nuclear translocation of the CRMP2 breakdown product was inhibited by DOPPA, calpeptin, and TAT‐CRMP2 in cortical neurons. In addition, both cPKCβ activation and CRMP2 proteolysis inhibition by hypoxic preconditioning and intracerebroventricular injections of DOPPA, calpeptin, and TAT‐CRMP2 improved the neurological deficit in addition to reducing the infarct volume and proportions of cells with pyknotic nuclei in the peri‐infact region of mice with ischemic stroke. These results suggested that cPKCβ modulates CRMP2 phosphorylation and proteolysis, and cPKCβ activation alleviates ischemic injury in the cultured cortical neurons and brains of mice with ischemic stroke through inhibiting CRMP2 proteolysis by phosphorylation. Focal cerebral ischemia induces a large flux of Ca 2+ to activate calpain which cleaves collapsin response mediator (CRMP) 2 into breakdown product (BDP). Inhibition of CRMP2 cleavage by calpeptin and TAT‐CRMP2 alleviates ischemic injury. Conventional protein kinase C (cPKC)β‐mediated phosphorylation could inhibit CRMP2 proteolysis and alleviate ischemic injury in cultured cortical neurons and ischemic stroke‐induced mice. Abstract : Focal cerebral ischemia induces a large flux of Ca 2+ to activate calpain which cleaves collapsin response mediator (CRMP) 2 into breakdown product (BDP). Inhibition of CRMP2 cleavage by calpeptin and TAT‐CRMP2 alleviates ischemic injury. Conventional protein kinase C (cPKC)β‐mediated phosphorylation could inhibit CRMP2 proteolysis and alleviate ischemic injury in cultured cortical neurons and ischemic stroke‐induced mice.